Echecs : Twenty Contemporary Artists. - Gallery Moving Space, Gent (Gent : Gallery Moving Space, 1990)
Dejean, Michel ; Bücheler, Josef ; Ceccobelli, Bruno ; Gangloff, Catherine ; Daquin, Pierre ; Roelstraete, Stefaan ; Berghe, Luk ; Decabooter, Lieven ; Sweetlove, William ; Deschuymer, Johan ; Wastijn, Koen ; Thinot, Dominique ; Albinet, Jean-Paul ; Moreau, Jean-Marc ; Taillandier, Yvon ; Viguie, Jean-Charles ; 't Kindt, Jacques ; Gauthier, Dominique ; Hoffmann, Godwin ; etc.
Echecs : Twenty Contemporary Artists, Gallery Moving Space, Gent, 19.05.1990 - 17.06.1990
boek